2020
DOI: 10.1002/cre2.362
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of patients subjected to direct and indirect pulp capping of young permanent teeth. A retrospective study

Abstract: Objective: A retrospective study of the success rate of direct pulp capping (DPC) and indirect pulp capping (IPC) was carried out in children between 6-14 years-old, considering separately primary caries or caries affecting teeth with molar incisor hypomineralization (MIH).Material and methods: Data were collected in a dental public health service. Following the inclusion criteria, 232 treatments were analyzed. Success was defined by the presence of a functional tooth without clinical signs or symptoms of pulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(41 reference statements)
0
1
0
1
Order By: Relevance
“…In the first instance, the article reported that the success rate of IPC and DPC was 99.4% and 84.6%, respectively. The median survival for DPC and IPC was 14.07 ± 1.30 and 15.98 ± 0.80 months, respectively [10] . Another article mentions that after 16 months, 95.83% of cases of teeth treated with biodentine showed successful results both clinically and radiographically.…”
Section: Permanent Teethmentioning
confidence: 97%
“…In the first instance, the article reported that the success rate of IPC and DPC was 99.4% and 84.6%, respectively. The median survival for DPC and IPC was 14.07 ± 1.30 and 15.98 ± 0.80 months, respectively [10] . Another article mentions that after 16 months, 95.83% of cases of teeth treated with biodentine showed successful results both clinically and radiographically.…”
Section: Permanent Teethmentioning
confidence: 97%
“…El estudio de la biología molecular podrá proporcionar excelentes resultados al tratamiento de la pulpa vital. Por otro lado, estudios adicionales son aún necesarios para garantizar la indicación de tratamientos con el uso de biomoléculas inductoras de reparación del complejo dentino-pulpar (Llena et al, 2021).…”
Section: Futuras Estrategias Para El Tratamiento Pulparunclassified